Genre Analysis of Article Abstract Sections across Translation Studies and English Literature - Malekzadeh, Maryam (LANGUAGE ART, 2020)
Research article abstract play a central role in enhancing the visibility of scientific work. As such, writing clear and informative abstract is of paramount importance for any academic discourse community. To contribute to the present body of research findings, the present investigation was conducted to explore the probable rhetorical differences between research article abstract sections across the two disciplines of English literature and translation studies with reference to Swales’ (2004) CARS model, an issue, which has not been addressed to date. Precisely, the study sought to discover what rhetorical structures characterize the article abstract sections written by translation and English literature researchers. The corpus featured 100 abstracts from both disciplines published in international journals that were analyzed in terms of the aforementioned model to unravel their underlying rhetoric structure. Overall, analyses revealed no significant cross-disciplinary difference between the rhetoric structures of the two sets of corpora except in terms of Step 1A of Move 2 (Indicating a gap). Specifically, it was found that the translation studies and English literature abstracts more often provided a clear reference to the primary purpose, principal outcomes, and methodology. To conclude, the pedagogical and theoretical significance of the findings were discussed in light of relevant theory and available research evidence.